Unlocking Auditor Potential: How Authentic Leadership Drives Work Engagement Through Meaning and Safety - Amar, Siti Salama; Kusuma, Adriani; Fajar, Achmarul (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This research is in the realm of management accounting with a focus on external auditor behavior as part of an organization's management control system. The purpose of this study is to analyze the effect of authentic leadership on auditor work engagement through the mediating role of work meaning and psychological safety. This study was conducted on 130 external auditors working in various public accounting firms in East Java. A quantitative approach was used in this study with the Partial Least Square Structural Equation Modeling (PLS-SEM) analysis technique. The results of the study indicate that authentic leadership has a significant effect on work meaning and psychological safety. These two mediating variables are then proven to have a positive effect on auditor work engagement. These findings provide theoretical contributions in expanding the management accounting literature, especially in the context of the influence of leadership behavior on psychological outcomes and non-financial performance of auditors. Practically, these results serve as an important reference for audit firm management in building a more authentic and supportive work culture in order to improve the performance and engagement of audit professionals. The conclusion of this study emphasizes the importance of authentic leadership as a managerial strategy to strengthen the quality of human resources in the audit sector.